COMPREHENSIVE MIDWIFERY CARE FOR RETAINED PLACENTA : A CASE STUDY IN 2026 - Sriyani, Himawari Kirina Petranela; Lestari, Gita; Pera, Rohani; Marliani; Lumbantoruan, Lenny M (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Retained placenta is a common obstetric complication during the third stage of labor and a major cause of postpartum hemorrhage, contributing significantly to maternal morbidity and mortality worldwide. It is defined as the failure of placental delivery within 30 minutes after fetal birth. Delayed management may lead to severe hemorrhage, hypovolemic shock, puerperal infection, disseminated intravascular coagulation, and maternal death. Therefore, comprehensive evidence-based midwifery care is essential to improve maternal outcomes. Objectives: This study aimed to describe the implementation of comprehensive midwifery care for Mrs. M, G3P1A1, diagnosed with retained placenta at T. Hutapea Independent Midwifery Practice (TPMB), Pematangsiantar City, Indonesia.Methods: A descriptive case study design was employed. Data were collected through history taking, physical examination, direct observation, medical record review, and clinical documentation. Midwifery care was provided using Varney’s Seven-Step Midwifery Management Process and documented using the Subjective, Objective, Assessment, and Plan (SOAP) format. Data were analyzed descriptively by comparing clinical findings with current evidence and national midwifery practice standards. Results: Mrs. M experienced retained placenta, indicated by failure of placental delivery more than 30 minutes after childbirth. Management included monitoring maternal vital signs, active management of the third stage of labor, assessment of uterine contractions and postpartum bleeding, preparation for manual placental removal, and collaboration with other healthcare professionals when indicated. Timely intervention resulted in successful placental delivery, adequate uterine contraction, controlled postpartum bleeding, and a stable maternal condition without complications. Conclusions: Comprehensive midwifery management based on clinical standards is essential for the early identification and effective management of retained placenta. Prompt intervention, continuous monitoring, and interdisciplinary collaboration contribute to preventing maternal complications and improving maternal safety.